2020
DOI: 10.1111/echo.14773
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular diastolic function in mitral stenosis

Abstract: The assessment of left ventricular (LV) function in the setting of mitral stenosis (MS) has been critically examined for decades. Accurate assessment of aberrations in diastolic function is important as these subjects often present with signs and symptoms of heart failure and pulmonary congestion that cannot be solely explained by the severity of mechanical obstruction. Echocardiographic evaluation of diastolic dysfunction includes an evaluation of reduced LV compliance, diminished restoring forces, and enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 61 publications
0
3
1
Order By: Relevance
“…McKay et al showed that there was either no change or minimal increase in LVED volume after balloon valvuloplasty in MS patients [ 30 ]. These findings contradict the reduced LVED theory [ 28 , 31 ]. Regardless of the mechanism, LV-GLS measurement can aid in detecting subclinical LV dysfunction in rheumatic MS patients with preserved EF.…”
Section: Discussioncontrasting
confidence: 60%
“…McKay et al showed that there was either no change or minimal increase in LVED volume after balloon valvuloplasty in MS patients [ 30 ]. These findings contradict the reduced LVED theory [ 28 , 31 ]. Regardless of the mechanism, LV-GLS measurement can aid in detecting subclinical LV dysfunction in rheumatic MS patients with preserved EF.…”
Section: Discussioncontrasting
confidence: 60%
“…Therefore, the authors concluded that E/SV ratio is more accurate to assess ele- vated LV filling pressures. 5 This is an important finding that can be easily applied in clinical practice during the assessment of patients with a possible diagnosis of HFpEF.…”
Section: Heart Failure Diagnosismentioning
confidence: 94%
“…4 In this issue of Echocardiography, Venkateshvaran et al assessed the accuracy of the ratio between mitral inflow velocity (E) and LV stroke volume (SV) (assessed by echocardiography) to identify patients with elevated LV filling pressure with passive leg lifting (PLL), compared to conventional echocardiographic variables. 5 They collected data from Doppler echocardiography and right heart catheterization, performed simultaneously in 37 patients with exertional dyspnea and in 26 healthy controls. During PLL, E/SV displayed stronger diagnostic ability to identify PCWP > 15 mmHg than E/e' (AUC = 0.94 vs. 0.81), mitral E/A ratio (AUC 0.76) and resting invasive PCWP (AUC 0.84).…”
Section: Heart Failure Diagnosismentioning
confidence: 99%
“…Despite the generational and geographic differences, in an advanced stage of the disease, enlarged LA and elevated RVSP may obscure the presence of quantifiable echo markers of LV diastolic dysfunction, thereby challenging the diagnosis of diastolic dysfunction. In this issue of the journal, Venkateshvaran and Govind 13 have reviewed the evidence thus far. They have shown that the isovolumic relaxation phase of the cardiac cycle may hold the key to assess elevated filling pressure in an overtly remodeled heart irrespective of the primary etiology of MS.…”
Section: The Right Ventricle and The Mitral Valve: Diastology Is Ubiqmentioning
confidence: 99%